A Educação ambiental e sua inserção no ensino formal - Guedes, José Carlos de Souza (2012)
Through education it is possible to transform the society we live in,making it conscious and clarifying the necessity to conserve and preserve the environment. This study was developed with the aim of analyzing Theenvironmental education in municipal schools Garanhuns / PE: perspectives of its application, aiming to investigate the main difficulties facts by teachings from public schools regarding the teaching of environmental education in the elementary school. For such a thing,a series of technical instrumental process was used. Firstly, there was an office study, with consisted of an essential step in search of atechnical theories for the progress of this research. Activities have developed, simultaneously, such as: reading and composition of bibliographicmaterial collected; creation of scheme graphic representation of the environmental education in elementaryschool municipal and governmental official institutions. Later on, the field practice has been done,with consisted in working the area of the research universe,aiming to produce direct observations, necessary to development of the research; interviewing and applying questionnaires, which permit the collection of some that qualitative and quantitative information. For such reason, the practice of teachers needs to be (re)analyzed, (re)thought,(re)tried, (re)elaborated and transformed intoa thought with historical bond contexts,being the dimension of the human being related and articulated with other institutions (the family, the church, the associations), aiming a major commitment in the education process towards the citizen formation.